A Global Revolutionary Class Will Ride the Tiger of Alienation - Hardy Hanappi (tripleC: Communication, Capitalism & Critique)
This paper investigates how the global class of organic intellectuals will emerge. It thus updates Marx view on class struggle dynamics of the 19th century by taking the quantum leap of productive forces during the last 200 years serious. The most striking new element is the tremendous increase of the force of information power brought about by ICT. The emergence of Fascism and Stalinism in the first half of the 20th century was just a frightening first symptom of the coming age of alienation. Today, basing class membership – including the emergence of class consciousness – only on the (physical) local position in industrial production units is insufficient, even misleading. Global production is by its inbuilt complexity blurring the visibility of a specific worker’s exploitation status. There is necessary alienation, but then class struggle managed disinformation and manipulation is added. For the progressive classes this implies that they are split along the lines of their respective education status – how far the fog can be dissolved. This is where the concept of the global class of organic intellectuals, of an avantgarde, enters. The paper shows that already in the emergence of this new socialist agent the structures, in particular the information structures, of the next mode of production have to be present. It turns out that features, which are evil for capitalist thought are often the most important ingredients for the constitution of the forerunners of a socialist global society: persistent contradictions and diversity, exploding oscillations, deep and time-consuming dialogues, irrational solidarity, aesthetic stubbornness. The new intellectuals can remain rooted in local circumstances, can be organic, because they share many of these features with the exploited classes within which they act as catalyst, as avantgarde. In the end global socialism, organised by a revolving class of organic intellectuals, has to master alienation. This is the challenge.